2023
DOI: 10.3390/su151511629
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Sustainable Use of Plastics in Horticulture—Perspectives, Innovations, Opportunities, and Limitations

Abstract: The use of plastics in horticulture is reviewed with respect to its sustainability based on the traditional criteria of triple Rs (reduce, reuse, and recycling) plus a re-place strategy, taking into account possible alternatives. Hail (and insect) nets made of HD-PE, with their long-term use mostly on apple and polytunnels of LD-PE for cherry and strawberry as well as solarisation mulches (reuse), were found to be relatively sustainable solutions for their needs and are currently without alternatives. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Generally, plastic waste mitigation strategies vary across locations globally. Many stakeholders consider that the adverse effects can be prevented using the "R" model (Refuse, Reduce, Redesign, Reuse, Recycle, and Recover) [295][296][297]. It can also be mitigated using the following recommendations:…”
Section: How Can We Sustainably Mitigate Plastic Pollution In Agricul...mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, plastic waste mitigation strategies vary across locations globally. Many stakeholders consider that the adverse effects can be prevented using the "R" model (Refuse, Reduce, Redesign, Reuse, Recycle, and Recover) [295][296][297]. It can also be mitigated using the following recommendations:…”
Section: How Can We Sustainably Mitigate Plastic Pollution In Agricul...mentioning
confidence: 99%
“…A substitute for agricultural development that prevents the buildup of MPs and NPs in soils might be bioplastics, particularly biobased and biodegradable ones [302,303]. Blanke [297] reported that many publications have addressed using substitute biodegradable polymers for the cultivation of several crops, primarily for short growing cycles on bare soils, although they are inappropriate for use as long-term coverings over uneven terrain. Their primary ecological and practical benefit is that they can be buried in the ground and left in the field for microorganisms to break down.…”
Section: How Can We Sustainably Mitigate Plastic Pollution In Agricul...mentioning
confidence: 99%